2012
DOI: 10.1080/02673843.2011.649399
|View full text |Cite
|
Sign up to set email alerts
|

Idol worship as compensation for parental absence

Abstract: Idol worship refers to psychological identification with and emotional attachment to an idol figure, who is most likely to be a celebrity for young people nowadays. Fragmentary findings in previous research on adolescent idol worship suggest that it may represent compensation for the worshipper's deficits, such as those in parental resources. To illuminate this compensation perspective, the study surveyed 401 Chinese secondary school students in Hong Kong. Its results show that parental absence and socioeconom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 32 publications
0
16
1
Order By: Relevance
“…McCutcheon et al (2016d) found that socioeconomic status was unrelated to CAS scores. However, Cheung and Yue (2012) found that idolisation of celebrities in adolescents was associated with lower parental socioeconomic status.…”
Section: Culturementioning
confidence: 95%
See 1 more Smart Citation
“…McCutcheon et al (2016d) found that socioeconomic status was unrelated to CAS scores. However, Cheung and Yue (2012) found that idolisation of celebrities in adolescents was associated with lower parental socioeconomic status.…”
Section: Culturementioning
confidence: 95%
“…Cheung and Yue (2012) found that celebrity idolisation was predicted by parental absencewhen the father or mother were absent, adolescents were more likely to idolise their favoured celebrity and also tended to have older idols, suggesting that a celebrity may serve as a kind of compensatory 'replacement' for a lack of authority figure. Scharf and Levy (2015) found that celebrity idolisation was associated with levels of preoccupation in the family (e.g.…”
Section: Parental Relationshipsmentioning
confidence: 99%
“…This is because the parental norms which facilitate adolescents' identity development would discourage young consumers from idol worship. Cheung and Yue (2012) also provided evidence that the absence in the adolescent's parental resources would prompt the young consumer to idolise star idols. These findings suggest that young consumers are likely to keep themselves away from idol worship because they find in their parental relationships that provide confidence and resource that support their identity development.…”
Section: Group Norms and Idol Worshipmentioning
confidence: 99%
“…Maltby et al (2004) found that personal worship was negatively related to the cognitive flexibility. This may imply that fans with high personal worship could be associated with low level of cognitive flexibility and they would be less likely than other people in possessing the mental capacity to adjust thinking or attention in response to changing goals or environmental stimuli (Cheung and Yue, 2012;Martin and Anderson, 2001). In other words, they lack the mental ability to adjust their thinking from old situations to new situations and therefore, would be very reluctant to overcome previously held beliefs or habits (Martin and Anderson, 2001;Martin, Anderson, and Thweatt, 1998).…”
Section: Personal Worship and Music Purchasementioning
confidence: 99%
“…Idolatry refers to psychological identification and an emotional attachment to an idol figure, which is probably a celebrity (Cheung & Yue, 2012) whose attachment is greatest with younger children, decreasing in intensity with age with females idolizing singers more than males (Raviv, Bar-Tal, Raviv, & Ben-Horin, 1996). Wang, Chen, Yang, and Farn (2009) also indicated that as fan idolatry increases, the willingness to commit digital piracy decreases and the willingness to purchase increases.…”
Section: Resultsmentioning
confidence: 99%